2017
DOI: 10.1159/000473887
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib versus Hepatic Arterial Infusion Chemotherapy as Initial Treatment for Hepatocellular Carcinoma with Advanced Portal Vein Tumor Thrombosis

Abstract: Objective: To investigate the validity of hepatic arterial infusion chemotherapy with low-dose 5-fluorouracil and cisplatin (LFP) versus sorafenib as first-line treatment for hepatocellular carcinoma (HCC) with portal vein tumor thrombosis (Vp3, Vp4). Patients and Methods: We retrospectively reviewed the cases of Child-Pugh A advanced HCC with Vp3 or Vp4 treated with LFP or sorafenib between October 2002 and December 2013. Results: There were 32 patients in the LFP group and 14 patients in the sorafenib group.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
63
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 16 publications
(28 reference statements)
4
63
2
Order By: Relevance
“…HAIC has been proposed to be beneficial for patients with advanced HCC owing to a numerically higher response rate than with sorafenib. We would like to share a unique case of a patient with advanced HCC and Child-Pugh (CP) class C liver reserve to endorse the findings of Moriguchi et al [1]. …”
mentioning
confidence: 58%
See 1 more Smart Citation
“…HAIC has been proposed to be beneficial for patients with advanced HCC owing to a numerically higher response rate than with sorafenib. We would like to share a unique case of a patient with advanced HCC and Child-Pugh (CP) class C liver reserve to endorse the findings of Moriguchi et al [1]. …”
mentioning
confidence: 58%
“…We read with great interest the study of Moriguchi et al [1] regarding the efficacy of hepatic arterial infusion of chemotherapy (HAIC) in treating advanced hepatocellular carcinoma (HCC) with portal vein tumor thrombosis (PVTT). HAIC has been proposed to be beneficial for patients with advanced HCC owing to a numerically higher response rate than with sorafenib.…”
mentioning
confidence: 99%
“…In a small retrospective series, Moriguchi et al [73] reported significantly longer survival in patients with tumour thrombus involving the main trunk and the first branches of the portal vein (types III and IV) treated with HAIC, compared to sorafenib, suggesting the use of HAIC is first-line in these patients, followed by sorafenib in case of no response.…”
mentioning
confidence: 99%
“…In our retrospective study, HAIC with the reservoir catheter system showed a relatively high response rate and improved prognoses in successful cases compared to the currently used systemic chemotherapy with sorafenib [2]. HAIC is not globally recommended as it has not been shown to be useful by randomized controlled trials; however, HAIC may be a useful treatment for advanced PVTT in HCC and is listed as a treatment option for HCC in the 2017 J-HCC clinical practice guideline.…”
mentioning
confidence: 99%
“…Although various systemic chemotherapeutic drugs are currently being developed, most target patients have Child-Pugh class A HCC. HAIC performed with the reservoir catheter system has been reported to be relatively safe, even in patients diagnosed with Child-Pugh class B [4], with relatively minor adverse events mainly including myelosuppression [1, 2]; there are successfully treated cases in which hepatic reserve improves. Therefore, in Child-Pugh class B or C HCC patients with advanced PVTT, if initial HAIC could successfully improve hepatic reserves to Child-Pugh class A under circumstances where the introduction of systemic chemotherapy is appropriate, for example in cases of extrahepatic spread, the therapeutic strategy of switching to systemic chemotherapy may be ideal.…”
mentioning
confidence: 99%